Analisis kemampuan literasi matematika siswa SMP Negeri 1 Juwana dalam menyelesaikan masalah matematika ditinjau dari adversity quotient - Antika Hananda Elya Adam; Ida Dwijayanti; Dhian Endahwuri (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2022)
Mathematical literacy has an important role in the world of education for the assessment of AKM. SMP Negeri 1 Juwana is in an effort to prepare AKM so that information related to mathematical literacy is needed. This study aims to describe the mathematical literacy ability of class VIII F students of SMP Negeri 1 Juwana with adversity quotient climbers, campers, quitters in solving the problem of building a flat side space. The method used in this research is descriptive qualitative. The data collection used are tests and interviews. The data analysis technique was carried out in 3 stages, namely data reduction, data presentation and conclusion drawing. Test the validity of the data using source triangulation by comparing data from 2 sources. The results showed that climbers students went through the process of formulating, applying, and interpreting mathematical literacy with 6 indicators completely. Campers students go through the process of formulating, applying and interpreting mathematical literacy, butwhen applying the concept by elaborating the completion steps in finding mathematical solutions it is not optimal, the interpretation that students write is not associated with real-world problems, the explanation of the reasons given does not make sense based on context. problem. Quitter students go through the process of formulating because students do not write anything on the answer sheet when designing strategies, the application of student concepts is not appropriate and only uses 1-2 steps of completion, students do not interpret the results obtained in the context of real-world problems, explanations of the reasons given students do not make sense based on context. Factors that affect mathematical literacy skills based on AQ are generally influenced by the lack of knowledge related to mathematical literacy, not being accustomed to working on mathematical literacy-type questions.